An invisible empire: on troubles in school - Marian Bielecki (Przestrzenie Teorii)
The article presents an interpretation of “school” scenes from Gombrowicz’s Ferdydurke which was inspired by Pierre Bourdieu’s sociological method. The use of concepts such as ‘habitus’, ‘reproduction’, and ‘pedagogical authority’ allows one to see not only a satire on didactic ineptitude, but also a thorough and acute analysis of the functioning of the school as an institution in these scenes. From this perspective, the key function of school is not to teach, but to reproduce the structure of the social order and implement performative pedagogy which shapes this community’s members.